A ecologia política nas ações dos movimentos socioterritoriais no Brasil : resistências contra os agrotóxicos e na defesa da agroecologia - Moura, Joana Tereza Vaz de; Cavalcante, Leandro Vieira; Mançano Fernandes, Bernardo (2023)
Considering the existence of a development model in the Brazilian countryside based on the exploitation of natural assets through the expansion of agribusiness, the article seeks to understand the resistance actions of socio-territorial movements in defense of agroecology and against the use of pesticides. The perspective of political ecology was adopted as a theoretical framework, contributing to highlight insurgent and emancipatory narratives. The information was collected by the DATALUTA Network database was adopted as an empirical reference, which deals with the actions of socio-territorial movements published in news portals between the years 2020 and 2021. From the analysis of these news, experiences were evidenced that are articulated in the fight against pesticides and in productive resistance in defense of agroecology, for example, strengthening the political ecology of resistance in the Brazilian countryside.
Considerando a consecução de um modelo de desenvolvimento no campo brasileiro baseado na exploração dos bens naturais mediante expansão do agronegócio, o artigo busca compreender as ações de resistência dos movimentos socioterritoriais na defesa da agroecologia e contra o uso de agrotóxicos. Adotou-se como referencial teórico a perspectiva da ecologia política, contribuindo para evidenciar práticas e narrativas insurgentes e emancipatórias. As informações foram coletadas pelo banco de dados da Rede DATALUTA, as quais versam sobre as ações dos movimentos socioterritoriais veiculadas em portais de notícias entre os anos de 2020 e 2021. A partir da análise dessas notícias, evidenciou-se experiências que se articulam na luta contra os agrotóxicos e na resistência produtiva em defesa da agroecologia, por exemplo, fortalecendo a ecologia política da resistência no espaço rural brasileiro.
Keywords: Social-territorial movements; Political ecology; Resistance; Pesticides; Productive resistance; Movimentos socioterritoriais^lpt; Ecologia política; Resistência; Agrotóxicos; Resistência produtiva